2020
DOI: 10.1055/s-0040-1715862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Newborns Born to SARS-CoV-2-Positive Mothers: A Retrospective Cohort Study

Abstract: Objective The novel virus known as severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has led to a terrifying pandemic. The range of illness severity among children is variable. This study aims to assess the characteristics of newborns born to SARS-CoV-2-positive women compared with those mothers who tested negative. Study Design This was a retrospective cohort study performed at Brookdale Hospital Medical Center in New York City from March to May 2020. Electronic medical records of mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 7 publications
2
34
1
4
Order By: Relevance
“…Farghaly and colleagues found that neonates born to mothers with laboratory-confirmed SARS-CoV-2 infection were more likely to have a cesarean delivery, lower APGAR scores, and a lower birthweight compared to neonates born to mothers without SARS-CoV-2 infection. 5 In our study, the birthweight of neonates born to mothers with laboratory-confirmed SARS-CoV-2 infection was 2.83 kg, and approximately 70% of these neonates were delivered via cesarean section.…”
Section: Discussionmentioning
confidence: 58%
“…Farghaly and colleagues found that neonates born to mothers with laboratory-confirmed SARS-CoV-2 infection were more likely to have a cesarean delivery, lower APGAR scores, and a lower birthweight compared to neonates born to mothers without SARS-CoV-2 infection. 5 In our study, the birthweight of neonates born to mothers with laboratory-confirmed SARS-CoV-2 infection was 2.83 kg, and approximately 70% of these neonates were delivered via cesarean section.…”
Section: Discussionmentioning
confidence: 58%
“…In a large American cohort, perinatal COVID-19 infection was estimated at 2.6% [108]. Most studies, however, report an infrequency of neonatal SARS-CoV-2 infection at birth or thereafter despite maternal infection of varying severity [1-3, 13, 16, 19, 20, 188,191,193,196,197,213,222,228,[237][238][239][240][241][242][243][244]. The latter has also been evident despite some newborn exposure to maternal breastfeeding [82,118,127,136,241].…”
Section: Neonatal Infectionsmentioning
confidence: 99%
“…In India, newborn infections were mild and selflimited [258]. The latter studies are contrasted to the report from Farghaly et al who found that newborns of COVID-19 infected mothers were more likely to have desaturations, have poor feeding, and be symptomatic during the first 2 weeks of post-natal follow-up [237]. Virus can be potentially found in both respiratory secretions and stool [260].…”
Section: Neonatal Infectionsmentioning
confidence: 99%
“…On the other hand, a less liberal approach for neonatal care is proposed by authors of the study by Farghaly et al [22], in which their analysis showed significant association between symptoms and SARS-CoV-2 status regarding skin-to-skin contact (p < 0.001). Both studied groups showed significant differences regarding isolation patterns (p < 0.001).…”
Section: Neonatal Care During Covid-19 Pandemicmentioning
confidence: 99%